Inherited metabolic diseases in the sudden infant death syndrome. Issue 11 (November 1991) - Holton, J B; Allen, J T; Green, C A; Partington, S; Gilbert, R E; Berry, P J
Abstract : All sudden, unexpected infant deaths presenting during a two year period within a defined geographical area in Avon and north Somerset were investigated for inherited metabolic disease. Of 95 deaths, 88 were classified as cases of sudden infant death syndrome (SIDS). In addition to the normal postmortem investigations, samples of cerebrospinal fluid, urine, vitreous humour, and skin were collected for metabolic studies. No abnormal organic acid metabolites were found in the fluids from the 88 cases of SIDS. Fatty acid oxidation was assessed in skin fibroblasts from 70 cases of SIDS, but no examples of medium chain acyl CoA dehydrogenase (MCAD) deficiency were found. One case with abundant glycogen in the liver was subsequently diagnosed as having glycogen storage disease type 1c. These findings suggest that the incidence of MCAD deficiency and other metabolic diseases in SIDS is much lower than previously claimed.